Sharing Sesion PKBM Pancasila: Menuju Masa Depan Hebat dimulai dari sekarang: Pengabdian Kepada Masyarakat Desa Sumur Batu Kec. Babakan Madang - Rini Nur Aini; Ajun Rois; Herlina Herlina; Bayu Segara Putra; Meira Diviana; Meysa Nurzahra; Moh. Rahman Harpian; Ifsya Zakyi Nadjira (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This community service program was conducted at a Community Learning Center (PKBM) located in Sumur Batu Village, Babakan Madang sub - district. The primary objective of this program was to provide motivation and inspiration for PKBM learners to develop a strong learning spirit and a clear vision for the future. Through an Educational Sharing Session entitled “Towards a Great Future Begins Now,” the learners gained insights into the importance of education as a foundation for achieving aspirations, as well as strategies for developing character and self-discipline. The activity employed interactive lectures and open discussions as its main methods of implementation. The results revealed an increase in leaners enthusiasm for continuing their education and planning for their future. They also demonstrated more positive attitudes toward learning and greater awareness of their personal potential. This program is expected to serve as an initial step toward building a resilient and competitive generation of lifelong learners within the community, particularly among the youth in Sumur Batu Village.